The Predictive Validity of Consensual and Unique Facets of Neuroticism, Conscientiousness, and Agreeableness in Five Personality Inventories. (June 2023) - Khoo, Shereen; Stasik-O'Brien, Sara M.; Ellickson-Larew, Stephanie; Stanton, Kasey; Clark, Lee Anna; Watson, David
Consensual facet structures help to unify a highly fractured personality literature, but mask information obtained from unique personality facets assessed by individual personality inventories. The current study identifies the consensual and unique facets of neuroticism, conscientiousness, and agreeableness based on analyses of five widely used personality inventories (Disinhibition Inventory-I [DIS-I], Faceted Inventory for the Five-Factor model [FI-FFM], HEXACO Personality Inventory—Revised [HEXACO-PI-R], NEO Personality Inventory-3 [NEO-PI-3], and Temperament and Affectivity Inventory [TAI]) in a community sample ( N = 440). Factor analyses revealed that neuroticism consisted of three consensual facets (distress/depression, anger, and sentimental anxiety) and four unique facets (shyness, regret/self-doubt, lassitude, and distractibility); conscientiousness consisted solely of four consensual facets (achievement striving, order, attentiveness, and responsibility); and agreeableness consisted solely of four consensual facets (prosociality, anger, venturesomeness, and trust). Regression analyses indicated that unique neuroticism facets predicted significant incremental variance across a range of psychological disorders. These results have significant implications for how neuroticism, conscientiousness, and agreeableness should be modeled at the lower order level in psychopathology research.